Joint distribution: service paradigm, key technologies and its application in the context of Chinese express industry. Issue 3 (3rd May 2020) - He, Yandong; Zhou, Fuli; Qi, Mingyao; Wang, Xu
ABSTRACT: To cope with the globalisation of online shopping, ecological environment deterioration and increasing traffic pressure, a novel logistics service paradigm – joint distribution (JD) – for tackling the bottlenecks in operational efficiency, quality of service and environment-friendly development is put forward under online shopping combining with the internet of things, service-oriented technologies and other advanced management methods and tools. Then, the concept of JD is defined under online shopping, the differences among JD, third-party express service system (TESS) and self-built logistics system (SLS) are discussed. JD architecture and typical characteristics and the key technologies for developing a JD service platform (JDSP) are introduced. Four core components, i.e. Management system, optimisation on resource service, operational strategies during the delivery, etc. are studied for developing the JDSP. Finally, we develop some key systems and integrate them into the JDSP, also the platform is applied to a joint distribution alliance, and future research directions are discussed.